Stereotactic Radiosurgery and Stereotactic Body Radiotherapy in the Management of Oligometastatic Disease. Issue 11 (November 2020) - Chen, H.; Louie, A.V.; Higginson, D.S.; Palma, D.A.; Colaco, R.; Sahgal, A.
Abstract: Stereotactic radiosurgery (SRS) and stereotactic body radiotherapy (SBRT) represent non-invasive, efficacious and safe radiation treatments for the ablation of intracranial and extracranial metastases. Although the use of SRS has been established by level 1 evidence for patients presenting with up to three or four brain metastases for at least a decade, the paradigm of ablating a limited number of extracranial metastases (typically up to five, known as oligometastatic disease) has yet to be proven beyond the few reported but highly encouraging phase II randomised trials. In this overview, we summarise the phase III randomised controlled trials evaluating SRS for intact brain metastases and postoperative surgical cavities and introduce the limited literature and future concepts for treating patients with more than five intracranial metastases. Next, we summarise the published phase II randomised controlled trials specific to SBRT and oligometastatic disease, while briefly describing and contrasting the technical principles and biological mechanisms of SBRT versus conventional radiation. Phase III evidence for SBRT is needed, and we summarise ongoing trials in this overview. Ultimately, SRS and SBRT have become cornerstone therapeutic options for patients with oligometastatic disease and the future is bright for these patients, considering that not so long ago they were considered incurable and relegated to palliation alone.